Successful treatment of Mucor circinelloides in a Burn patient - Reham Abdelmonem (Burns Open, 2022)
Mucormycosis is a rare disease, which has a poor prognosis among burn patients with a reported mortality of 40–88%. We report on the survival of a 54-year-old male patient with burns of 50% of his total body surface area (TBSA) who survived despite rapid deterioration following cutaneous and probable systemic mucormycosis. A combination of antifungal treatment with extensive debridement and amputation likely resulted in the positive outcome in this case.The case highlights the importance of early diagnosis, antifungal treatment, and aggressive surgical management in burn patients with mucormycosis.